CULTURAL COMMUNICATION IN THE ASPIRATIONS OF SUBAK JATILUWIH FARMERS TOWARDS TRANSFER OF LAND FUNCTIONS AND SHARING OF MANAGEMENT RESULTS OF DTW JATILUWIH - Maulana Sandijaya (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
This research examines the aspirations of farmers in Subak Jatiluwih regarding land conversion and profit sharing for the management of the Jatiluwih tourist attraction (DTW), in Jatiluwih Village, Penebel District, Tabanan Regency, Bali. This research is important to carry out, because based on brief observations and in-depth interviews with Subak or Pekaseh clients, it was found that there was a gap between ideal conditions (das sollen) and reality (das sein). Farmers as cultivators and owners of rice fields feel that they have received unfair treatment, especially in terms of pahpahan or the profit sharing system which originates from the Jatiluwih DTW ticket levy. Profit sharing itself involves the Tabanan Regency Government (Pemkab), Jatiluwih DTW Management, traditional villages, and farmers. The farmers in Subak Jatiluwih, as owners and cultivators of 227 hectares of rice fields, feel they are only being used as a tourist attraction. Farmers are also worried about land conversion. There are at least two restaurants standing in Subak Jatiluwih. The existence of these two restaurants was also the main focus of the UNESCO delegation at the WWF Summit in May 2024. Farmers are worried that if land conversion continues, the area of ​​Subak will narrow and the WBD status could be revoked by UNESCO. The research question is, how is the profit sharing system determined, so that farmers feel unfair? Second question, how does the land conversion occur? To answer this question, researchers used qualitative research methods by interviewing farmers as primary data and conducting literature studies from reports in the mass media as secondary data. The primary and secondary data were then analyzed using interpretive descriptive techniques. Meanwhile, the theory used by researchers is a postmodern approach, with Michael Foucault’s theory of power-knowledge relations.